(untitled) (Innovaciones Educativas, 2024)
The Costa Rican educational system has seen an increase in the number of educational options for secondary education; however, there is a lack of clarity regarding the different offerings and modalities available. For this paper, we interviewed school principals, educational circuit supervisors, and administrative personnel from the central offices of the Costa Rican Ministry of Public Education (MEP) to answer the following research questions What are the criteria used to change or introduce educational modalities and offerings in secondary education in Costa Rica? What are the administrative and curricular management processes to approve the introduction or modification of modalities and offerings? And finally, how can we describe the process to introduce changes or new modalities or offerings in the MEP? This study used a descriptive/exploratory methodology, including interviews and documentary analysis. In terms of curricular and administrative management, the study found that there is no clear typification of these educational proposals, nor is there a clear process for the introduction, modification and closure of such educational options. The administrative and curricular management is complex, as it involves different departments within the MEP, which do not always have the necessary coordination, and that there are a number of possible processes to introduce, modify and close educational modalities and offerings, also budgets play a key role in the approval of such proposals. These findings are discussed in the light of the right of individuals to quality education and to fully develop their educational and professional potential.